2008
DOI: 10.1373/clinchem.2007.089896
|View full text |Cite
|
Sign up to set email alerts
|

P-Selectin–Coated Microtube for Enrichment of CD34+ Hematopoietic Stem and Progenitor Cells from Human Bone Marrow

Abstract: Background: Enrichment and purification of hematopoietic stem and progenitor cells (HSPCs) is important in transplantation therapies for hematologic disorders and in basic stem cell research. Primitive CD34+ HSPCs have demonstrated stronger rolling adhesion on selectins than mature CD34− mononuclear cells (MNCs). We have exploited this differential rolling behavior to capture and purify HSPCs from bone marrow by perfusing MNCs through selectin-coated microtubes. Methods: Bone marrow MNCs were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 20 publications
1
56
0
1
Order By: Relevance
“…Therefore, PEGylation of the particles is important for stability under flow and target specificity. Consistent with our previous reports, 19,25 large numbers of cells were captured from flow by the PS-DSPE-PEG-NP surface. Although P-selectin-based cell capture is also associated with inflammation of the liver or lung in vivo, our previous work in rats has shown that the risk of systemic inflammatory conditions will be minimal due to the lack of inflammatory chemokines and b-2 integrin ligands on the device surface.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, PEGylation of the particles is important for stability under flow and target specificity. Consistent with our previous reports, 19,25 large numbers of cells were captured from flow by the PS-DSPE-PEG-NP surface. Although P-selectin-based cell capture is also associated with inflammation of the liver or lung in vivo, our previous work in rats has shown that the risk of systemic inflammatory conditions will be minimal due to the lack of inflammatory chemokines and b-2 integrin ligands on the device surface.…”
Section: Discussionsupporting
confidence: 92%
“…On the basis of our previous results, 25 we expected that 26 After cellular perfusion, a near monolayer of HL60 cells was tethered (Figure 5d) and accompanied by a thin layer of PS-DSPE-PEG NPs absorbed onto the inner surface of the microtube (Figure 5c). Furthermore, the coated PS-DSPE-PEG NPs were released with the tethered cells by higher shear stress and air embolism from the microtube surface (Figures 5e and f).…”
Section: Hl60 Cells Captured From Flowmentioning
confidence: 62%
See 1 more Smart Citation
“…Researchers have also investigated the possibility of separating cells based on rolling, including a technique for capturing cells in microfluidic devices 24,25 and separation of cells based on differential rolling velocities in a flow chamber 23 . Separation based on cell rolling is applicable to a wide range of cell types such as leukocytes, hematopoietic stem/progenitor cells, and metastatic cancer cells [19][20][21]25 . Recent work has also shown that co-immobilization of selectins and antibodies that are specific to molecules expressed on the cell surface can affect the rolling behavior of cells, further enhancing the utility of rolling-based separation 26 .…”
mentioning
confidence: 99%
“…1961: Demonstration of the existence of stem cells (2) 1981: First culture of pluripotential cells from mouse embryos (4) 1998: human Embryonic Stem Cell line (6) 2006: Induced Pluripotent Stem cells (iPSC) from mice (7) 2008: -Obtention of iPSC with c-Myc infection (11) -Use of iPSC in an animal model of Parkinson's disease (12) 2010: Obtention of iPSC only with Oct4 and chemical compounds (13) 2016: Complete reconstitution of pupps starting from skin cells (17) 1958: First use of a nuclear transfer approach in tadpole (1) 1974: First transgenic mice (3) 1996: Cloning of Dolly (5) 2007: -Yamanaka's factors to obtain iPSCs (8) -Obtention of humain iPSCs from human somatic cells (9) -Use of iPSC technology to treat sickle cell disease in mice (10) HSC engraftment, including selectin modifications or fucosylation of HSCs (38). Lastly, molecular mechanisms controlling HSC fate determination must be fully deciphered as well as understanding the complexity of HSCs due to their heterogeneity.…”
Section: Hscs: a Pioneer Tool For Regenerative Medicinementioning
confidence: 99%